Will Consolidation Improve Sub-National Governments? - Fox, William F.; Gurley, Tami (World Bank, Washington, DC, 2012)
Local government size varies dramatically around the world. In Sudan, Cote d'Ivoire, and the United Kingdom, municipalities average more than 125,000 people. Those in many European countries have less than 10,000 people. Countries often consider consolidation of local governments as a means to lower service delivery costs, improve service quality, enhance accountability, improve equity, or expand participation in government. The authors review a number of theoretical arguments and empirical findings concerning the size of sub-national governments. Countries should not presume that amalgamation will solve problems because benefits and costs are situation specific. Success depends on many factors, including getting incentives right for the various players and managing the transition properly. The effects on costs must be examined in terms of all changes occurring with consolidation, including geographic size. Size economies appear service specific and are most likely to result for infrastructure intensive services such as water and sewerage. Size economies are less likely for services such as education that are provided in numerous small production units near the population. Also, the potential for savings depends on other factors, such as willingness to eliminate redundant workers. Consolidation reduces the potential for local government competition, which appears to enhance service quality but not necessarily overall government size. There is some evidence that citizens are more willing to be involved in larger governments, but trust may fall with government size. Larger governments can improve regional planning by handling problems with a broader geographic perspective and giving the government more influence with national policymakers.